Community center. - (:unkn) unknown (Jovis, 2018)
speech: 21 widmet sich der Bauaufgabe Gemeinschaftszentrum. Welche Funktion und Form muss ein solches heute haben, um Anwohner zusammenzubringen und sie bei der Bewältigung sozialer Fragen zu unterstützen? Und wie verändern sich Gemeinschaftszentren je nach Größe und Lage eines Wohnviertels?

The twenty-first issue of speech: studies the phenomenon of the community center. What functions and what forms must community centers have today in order to continue to bring people and communities together and help them tackle socially important issues, and how do these change depending on the scale and geography of their surrounding?
Keywords: Architektur; Gemeinschaftszentrum; Sozialinfrastruktur; Soziokultur; Urban Farming; Gemeindezentrum; Kulturzentrum; Bauaufgabe; Internationaler Vergleich; Beispielsammlung